Inclusive Practices for Deaf Children in Elementary Education: Insights from a Literature Review - Anfal Zaeni Noor; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
Inclusive education seeks to ensure equitable access to learning for all students, including those who are deaf or hard of hearing. Despite its growing adoption, the implementation of inclusive practices in Indonesian elementary schools continues to face significant challenges, such as limited teacher competence, inadequate infrastructure, and minimal social support. This study aims to identify effective learning strategies for deaf students within inclusive education settings by conducting a systematic literature review with a qualitative approach. A total of 20 primary sources published between 2011 and 2024 were analyzed. The findings reveal that multisensory approaches, mnemonic techniques, and differentiated instruction significantly improve language acquisition and social skills among deaf students. However, the implementation is hampered by barriers such as insufficient teacher training in sign language, substandard acoustic classroom conditions, and low levels of parental engagement. To address these issues, this study recommends the integration of digital technologies, comprehensive teacher training initiatives, and the development of data-driven educational policies. The results align with Vygotsky’s socio-emotional development theory, highlighting the critical role of social interaction in learning. This study contributes to advancing inclusive education theory and offers practical strategies to enhance the educational experiences of deaf students. Further research through longitudinal studies is suggested to evaluate the sustainability and long-term impact of these strategies.